Drivers of Australian dust: a case study of frontal winds and dust dynamics in the lower lake Eyre basin. Issue 14 (25th August 2015) - Baddock, Matthew; Parsons, Katherine; Strong, Craiq; Leys, John; McTainsh, Grant
Abstract The roles of pre‐frontal, frontal and post‐frontal winds as the primary wind systems for dust entrainment and transport in Australia are well established. While the relevance of each system has been observed across different wind erosion events in central Australia, the entrainment of dust by all three winds during the passage of an individual front has not been demonstrated until now. Synoptic information, satellite aerosol and imagery, meteorological and dust concentration data are presented for a single case study erosion event in the lower Lake Eyre Basin. This event demonstrates variable dust transport in three different directions from one of the southern Hemisphere's most significant source regions, and the changing nature of the active dust pathways during the passage of a frontal system. While only a single dust event is considered, the findings show the complexity of mineral aerosol emission and transport patterns even within an individual dust outbreak. For the lower Lake Eyre Basin, this appreciation of pathway behaviour is significant for better understanding the role of aeolian inputs from the dominant Australian source to surrounding marine systems. In a wider context, the findings exhibit the detailed insights into major dust source dynamics that can be obtained from high resolution spatial and particularly temporal data, as used in combination. This work highlights the importance of adequately resolved data for the accurate determination of dust entrainment and transport patterns of major dust sources. Copyright © 2015 John Wiley & Sons, Ltd.